DESCRIPTION OF DEVELOPMENT CHILDREN AGE 24 – 59 MONTH - Tabah, Hikmah Mesti; Widiasih, Restuning; Ermiati, Ermiati (Journal of Maternity Care and Reproductive Health, 2022)
Screening development for children is important to detected any developmental problem in children. Early detection in children development would provide early intervention if Wanaraja there are development problem. Therefore the aims of this study is to assess the development of children age 24 - 59 months This research was descriptive quantitative research, The sample in this study were 56 children age 24 – 59 month. The study was conducted in village, Karangpawitan sub-district, Garut city. The samples were choosen using consecutive sampling technique, and the data were collected with visit the posyandu.the Instrumen of this study was Kuisioner Pra-Skrining Perkembangan (Pre-Screening Development questionnare). The results showed that 60.7% of children development is normal, 30.4% doubting, and 8.9% have developmental problem. The conclusion, there are children in doubting and development problem category and need special attention. Recommendation, health workers is expected to provide further nursing intervention to children and parents especially for children with development problem.